Regional brain serotonergic activity as an indicator of chronic stress and compromised welfare in fish - Sørensen, Christina; Vas, Judit; Folkedal, Ole; Bui, Samantha; Remen, Mette; Gunnes, Mikkel; Calabrese, Sara; Wedaa, Louise O. M.; Green, Evelina A. L.; Øverli, Øyvind; Höglund, Erik (Frontiers in Endocrinology, 2026)
BackgroundChronic stress in aquaculture poses major challenges to fish welfare, health, and productivity. Detecting compromised welfare early requires validated biomarkers that link operational welfare indicators (OWIs) to underlying neuroendocrine states, including allostatic load and stress coping capacity. The central serotonergic system is a promising candidate for such validation, given its conserved role in stress regulation across vertebrates.MethodsWe sampled 40 Atlantic salmon (Salmo salar) from research-scale sea cages spanning a wide range of welfare states under production-relevant conditions. Fish were exposed to acute crowding during routine rearing operations immediately prior to sampling. Plasma cortisol was measured, along with serotonin (5-HT) concentration and turnover, proxied by 5-hydroxyindoleacetic acid (5-HIAA) and the 5-HIAA/5-HT ratio, in the brain stem and telencephalon. Associations among 5-HTergic variables, welfare indicators (OWI sum, scale loss, condition factor), and acute stress metrics (crowding time, cortisol) were analysed using principal component analysis (PCA), multivariate analysis of variance (MANOVA), and post hoc linear models.ResultsBrain stem 5-HT concentration and turnover were consistently associated with welfare-related indicators and loaded strongly with these variables in multivariate space, indicating sensitivity to cumulative stress and compromised welfare. In contrast, telencephalic 5-HT turnover aligned primarily with acute stress metrics rather than welfare state. MANOVA and post hoc analyses confirmed these region-specific associations. A significant interaction for telencephalic 5-HIAA revealed that fish in poorer welfare states exhibited a blunted 5-HTergic response to acute stress compared with individuals in better welfare condition, consistent with reduced stress responsiveness under chronic strain.ConclusionOur findings demonstrate a clear regional dissociation in central 5-HTergic stress processing in Atlantic salmon: brain stem 5-HT activity reflects chronic stress burden and welfare state, whereas telencephalic 5-HT turnover reflects acute stress reactivity conditional on baseline welfare. These results support the use of region-specific 5-HTergic measures as biologically grounded markers distinguishing chronic welfare compromise from functional acute stress responses in aquaculture, while emphasizing caution when interpreting acute stress reactivity in chronically stressed individuals.